2014
DOI: 10.4174/astr.2014.87.6.340
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy performed in a patient with situs ambiguous accompanied with isolated levocardia, malrotation, and normal spleen

Abstract: We report a case of common bile duct (CBD) cancer, successfully managed with pancreaticoduodenectomy, in a patient with isolated levocardia, malrotation, and situs ambiguous (without splenic anomalies). A 59-year-old male patient was referred to Chung-Ang University Hospital with epigastric pain and jaundice. CT and MRI revealed distal CBD cancer without significant lymphadenopathy. Multiple abdominal anatomic anomalies were identified preoperatively, whereas no anatomic anomalies were detected within the ches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
2
0
2
Order By: Relevance
“…Additionally, the small bowel was also normally positioned, in keeping with same pattern described before in a similar case [3], in contrast to other reports that found intestinal mal-rotation or non-rotation with heterotaxy patients [1,7,14]. Interrupted or absent IVC with azygous or hemi-azygous veins continuation is a constant associated finding with heterotaxy syndrome [3,15].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the small bowel was also normally positioned, in keeping with same pattern described before in a similar case [3], in contrast to other reports that found intestinal mal-rotation or non-rotation with heterotaxy patients [1,7,14]. Interrupted or absent IVC with azygous or hemi-azygous veins continuation is a constant associated finding with heterotaxy syndrome [3,15].…”
Section: Discussionsupporting
confidence: 87%
“…However, no report on the reconstruction procedure was found. We conducted a review of literature that included Japanese studies by searching the PubMed database, and we found reports on a total of 16 patients with intestinal malrotation who underwent pancreaticoduodenectomy (Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. None of the 16 patients developed any complication associated with reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are some previous reports of complicated pancreatic and hepatic surgeries in patients with heterotaxy syndromes that described technical difficulties and risks encountered during that operations because of the aberrant anatomy [7][8][9][10]; there are no previous reports of a laparoscopic hiatus hernia repair in a patient with heterotaxy syndrome in the reviewed English literature, and this reported case demonstrates the operative challenges and complexities that are usually faced during a surgical procedure that is already described as a kind of difficult surgeries in the field of laparoscopic hernias repair, that-in fact-requires a precise understanding of the surrounding anatomy of the gastroesophageal junction and esophageal hiatus [11].…”
Section: Discussionmentioning
confidence: 99%